"Gamelan dan Energi" Karya Musik Baru Untuk Gamelan dan Perangkat Elektronik - I Kadek Janurangga; I Wayan Diana Putra (Jurnal Riset dan Pengabdian Masyarakat, 2022)
The existence of Gamelan which assisted by today’s digital media is attract the enthusiasm of many people from all generations. With the presence of digital media as a tool that makes it easier to work in the creation of art, the music industry is expanding. Apart from that, the electronic music presented by an idealist person has purpose and intent of sound that is outside the industrial habits that occur. Gamelan and Energy is an art work designed on the basis of the creator's awareness that the presence and advancement of technology must coexist with the traditions inherent in society. Movement and development became a strong foundation for designing and creating this work. The elaboration of traditional Balinese creation methods and music creation methods by Roger Session became the basis for the process of forming this work. Electronic devices and acoustic instruments in the form of gamelan are used as the medium of expression in this work. Gamelan as an object of the sound reality is the basis of footing and Energy as power or strength in carrying out a form of development that refers to the existence of the subject in this work. In addition, energy as power or strength is also presented in electronic devices as a medium for manipulating sound. Each part of the compositional structure in this work implements a process of creating music based on movement and development.